PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP MINAT MAHASISWA BERWIRAUSAHA - Moh. Ubaidillah; Supri Wahyudi Utomo (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
This study aims to determine and obtain empirical evidence about the influence of problem-based learning model of entrepreneurship interest in students. This research is also to know the result of student learning. This type of research is ex post facto and sampling method using quota sampling method as much as 32 students of class D semester 4 of accounting education program of Universitas PGRI Madiun. Data collection techniques of this study using questionnaires and student learning outcomes. Data analysis method of this research questionnaire using structural equation modeling (SEM) with partial least squares (PLS) tool. The results showed that the problem-based learning model positively affects entrepreneurship interest. Furthermore, student learning outcomes show that the overall score of students above achievement criteria.